Determinants of inflation in Singapore. - Eu, Cheng Joo. (2008)
Even with a record of low inflation, the unique economic structure of Singapore could pose threats to its stability. This study seeks to examine the price level equation of Singapore. Through investigating the determinants of Singapore’s inflation, this paper discusses some macroeconomic policy management implications for small and open economies.